2019
DOI: 10.1088/1361-6420/ab30f3
|View full text |Cite
|
Sign up to set email alerts
|

Transform-based particle filtering for elliptic Bayesian inverse problems

Abstract: We introduce optimal transport based resampling in adaptive SMC. We consider elliptic inverse problems of inferring hydraulic conductivity from pressure measurements. We consider two parametrizations of hydraulic conductivity: by Gaussian random field, and by a set of scalar (non-)Gaussian distributed parameters and Gaussian random fields. We show that for scalar parameters optimal transport based SMC performs comparably to monomial based SMC but for Gaussian highdimensional random fields optimal transport bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…According to the theory in [27], α n must be carefully selected, together with the stopping criteria, in order to ensure the stability of the LM scheme. The approach for selecting α n in the LM proposed in [27] has been adapted to the EKI framework in [2,16], and subsequently used in [3,12,14,[28][29][30]. As we discuss in the next section, this approach relies on tuning parameters that, unless carefully chosen, can lead to unnecessary large number of iterations n * .…”
Section: The Inverse Problem Framework With Ensemble Kalman Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the theory in [27], α n must be carefully selected, together with the stopping criteria, in order to ensure the stability of the LM scheme. The approach for selecting α n in the LM proposed in [27] has been adapted to the EKI framework in [2,16], and subsequently used in [3,12,14,[28][29][30]. As we discuss in the next section, this approach relies on tuning parameters that, unless carefully chosen, can lead to unnecessary large number of iterations n * .…”
Section: The Inverse Problem Framework With Ensemble Kalman Inversionmentioning
confidence: 99%
“…where we have made the standard assumption that y = G(u) + η with η ∼ N(0, Γ). Modern computational approaches [28,[32][33][34][35] for high-dimensional Bayesian inverse problems use the tempering approach that consists of introducing N intermediate measures {μ t n } N n=1 between the prior and the posterior. These measures are defined by…”
Section: Eki As a Gaussian Approximation In The Bayesian Tempering Sementioning
confidence: 99%
“…1 a and b and as it has been reported in the literature, e.g. [28,29]. When uncertainty is in both permeability and boundary conditions, we investigate methods performance for two numerical setups.…”
Section: Data Assimilation Without Localizationmentioning
confidence: 93%
“…We have shown that though localization makes the ensemble transform particle filter deteriorates a posterior estimation of the leading modes, it makes the method applicable to highdimensional problems. In [29], instead of localization, we have implemented tempering to the ensemble transform particle filter (TETPF). We have shown that iterations based on temperatures [21,23] handle notably strongly nonlinear cases and that TETPF is able to predict multimodal distributions for high-dimensional problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation